Syrah and Grenache (Vitis vinifera) revealed different strategies to cope with high temperature - Gallo, Agustina Eugenia; Perez Peña, Jorge Esteban; Gonzalez, Carina Verónica; Prieto, Jorge Alejandro (Australian Society of Viticulture and Oenology, 2022)
Background and Aims: Global warming will threaten vineyard sustainability in warm and arid regions. Therefore, increasing water use efficiency (WUE) is essential for long-term viticulture sustainability. Nevertheless, studies concerning the response of stomata and WUE to temperature are scarce. We evaluated the effect of sustained warming on WUE and its components in cultivars with contrasting stomatal behaviour. Methods and Results: We applied a 1.1 C increase in field-grown, well-watered plants, during the growing season and compared them to Control plants. We measured net assimilation (An), transpiration rate (E), stomatal conductance (gs), stomata density and length, intrinsic and yield WUE (WUEint and WUEyield). Gas exchange and WUEint in response to heating were cultivar-dependent. Heated Grenache plants increased An, gs, E and stomatal length but decreased WUEint. In contrast, gas exchange and WUEint were similar between heated Syrah and Control plants. Both cultivars decreased WUEyield in response to heating. Conclusions: An increase in air temperature decreased WUEint in Grenache, whereas Syrah could tolerate heating without modifying leaf functioning. We proposed these strategies to cope with heating as ‘avoiding’ for Grenache and ‘tolerant’ for Syrah in well-watered conditions. Significance of the Study: This research contributes to an understanding of the strategies to cope with high temperature of different cultivars, which should be considered to select better-adapted genotypes for the expected warmer conditions.